Spondyloarthrites au Sénégal: Étude de 350 Observations - Condé Kaba; Niasse Moustapha; Garba Mahaman Salissou; Diallo Rama; Diaw Cheik Amadou Bamba; Diouf Coumba; Diallo Saïdou (European Scientific Journal, ESJ, 2019)
Objective: Spondyloarthritis is classically considered rare in subSaharan Africa where the majority of the population is considered to be HLAB27 negative. Thus, this series allows us to describe the characteristics of SpA in one Senegalese hospital. Patients and methods: Retrospective and descriptive study carried out in the Rheumatology Department of the University Hospital of Dakar. The diagnosis of SpA was retained in accordance with the ASAS and modified New York criteria. For each patient, the following data were collected: age, sex, time to diagnosis, type of SpA, nature of joint involvement: axial, peripheral, extra-articular manifestations, HLA B27 phenotyping. Results: 350 observations of SpA were collected in 228 women (65%) with a mean age of 47 ± 13. The average time to diagnosis was 11 years. AS was the most common: 71.2%, reactive arthritis 8.3%, psoriatic arthritis 6%, IBD 2.6%, SAPHO and undifferentiated forms 2.7%. HLA B 27 phenotyping was performed in 213 patients, 115 patients were HLA B27 positive (50.7%). Treatment was based on nonsteroidal antiinflammatory drugs (47.71%). Conclusion: SpA is growing in a Senegalese hospital. They hit especially the middle aged woman of 46 years old. AS is the most common form of SpA. HLA B27 is present in about in 1 out of 2 patients.Objectif: Les spondyloarthrites sont classiquement considérées comme rares en Afrique sub-saharienne où la majorité de la population est considérée comme HLA-B27 négatif. L’objectif de notre étude était de décrire les caractéristiques des SpA en milieu hospitalier sénégalais. Patients et méthode: Ils’agissait d’une étude rétrospective réalisée dans le service de rhumatologie du CHU Le Dantec de Dakar. Le diagnostic de SpA était retenu en accord avec les critères d’ASAS et de New York modifié. Pour chaque patient, les données suivantes ont été collectées : l’âge, le sexe, le délai au diagnostic, le type de SpA, la nature de l’atteinte articulaire : axiale, périphérique, manifestations extra-articulaires, le phénotypage HLA B27. Résultats: Avaient été colligées 350 observations de SpA chez 228 femmes (65 %) d’âges moyen de 47 ±13 ans. Le délai moyen au diagnostic était de 11 ans. La SA était la plus fréquente : 71,2 %, ARé 8,3 %, le RP 6 %, les MICI 2,6 %, le SAPHO et les formes indifférenciées 2,7 %. Le phénotypage HLA B 27 était réalisé chez 213 patients, 115 patients étaient HLA B27 positifs (50,7%). Le traitement était basé sur les AINS (47,71%). Conclusion : Les SpA sont en croissance en milieu hospitalier Sénégalais. Elles sont surtout fréquentes chez la femme. La SA est la SpA la plus fréquente et l’antigène HLA B27 est présente chez environ 1 patient sur 2.